Investigation of Matrix Metalloproteinase-2 and 9 in Patients with Chronic Renal Failure - Abdulameer, Hala Basil; Ismael, May Khaleel (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The family of zinc-dependent endopeptidases known as matrix metalloproteinases (MMPs) has been linked to both healthy and unhealthy kidney physiology. Members of the MMP family known as gelatinases (MMP-2, MMP-9) are essential for the degradation of the extracellular matrix (ECM). This effect plays a significant role in the progression of chronic kidney disease (CKD).and as an indicator of chronic renal failure (CRF), which is a permanent loss of kidney function that occurs when the glomerular filtration rate (GFR) falls below 60 ml/min/1.73 m² for more than 3 months. The presented study was established to investigate the MMP-2 and -9 concentrations in the urine and serum among Iraqi patients with CRF undergoing regular weekly dialysis at the Hamida Al-Misfaa dialysis center of Al-Kadhimiyah Educational Hospital as well as the dialysis center of AL Yarmouk Hospital in Baghdad between November 2022 and January 2023. Detection was done using the sandwich enzyme-linked immunosorbent assay technique. The results indicated that MMP-2 and MMP-9 expression levels in both serum and urine were considerably higher in-patient groups compared to healthy individuals